Preventive activities in the area of indebtedness in socially excluded localities and schools - Stoeva, Petra; Hůlová, Gabriela (Univerzita Pardubice, 2010)
This contribution represents projects focused on preventive activities in the field of indebtedness and distraint. In the introduction, the reader is introduced to the problems of indebtedness. The next section describes the preventive activities aimed at those living in socially excluded localities. This is followed by introduction of a preventive program for high schools and secondary vocational schools. Conclusions are based on experience gained through social work provided to families by municipality and non-profit organisation specialising in dealing with debt counselling. Observations from the experience and other visions are presented at the end of the chapters on implementation of the project.
Keywords: debt; executions; prevention; project; social work